MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN MELALUI PERMAINAN BOLA BASKET DI KB HARAPAN BANGSA DESA PANTAI CERMIN KABUPATEN KAMPAR - Herli Marlina; Tri Umari; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims to improve the gross motor skills of children aged 4-5 years through ball game basketdi KB Harapan Bangsa Desa Pantai Cermin Kampar regency. Research carried out directly in KB Harapan Bangsa Desa Pantai Cermin. Subject Research is a group A1 KB Harapan Bangsa 4-5 year age child who numbered 13 consists of six men and seven women in the second half of April Year 2016. The experiment was conducted in two cycles, each cycle consisting of three sessions covering planning, implementation, observation and reflection. This study collected data using observation and statistically analyzed descriptively so that the initial data values obtained 40.87% karegori starting to develop, in the first cycle values obtained an average of 51.04% and the second cycle values obtained an average of 76.76% a category is growing very nice. Shows that use of the game of basketball can improve gross motor skills of children.Keywords: Basketball Games, Kids Gross Motor.